PERBANDINGAN PENERAPAN METODE DISCOVERY-INQUIRY TERBIMBING DENGAN METODE CERAMAH BERVARIASI TERHADAP HASIL BELAJAR SISWA SMA KELAS X - Jaya, Aryanti Indah; Taiyeb, A Mushawwir; Hartono, Hartono (Universitas Sebelas Maret, 2013)
This is quasy experimental research, which aims to know the comparison of students learning’s achievement by using variated speech method and guide inquiry - discovery. The population of this research was all students at X in senior high school 2 Palopo at academic year 2012/2013 consisting of nine classes. The sample of this research are X9 experiment class with guide discovery-inquiry method and X8 as control class with variated speech method. The measurement of learning achievement was done by giving achievement test are multiple choice. The collected data were analyze using descriptive statistic and inferential statistic using t-test with the significant level of 0,05. Average score for experiment class with teach by guide discovery-inquiry method is 82,58 and control class with teach by variated speech method is 76,87. The statistic result of t-test (α = 0,05) showed the value sig (2-tailed) 0,00 < α (0,05) then the hypothesis H0 was rejected and H1 was accepted. This research conclude that there is different of students learning achievement by using guide discovery-inquiry method acquire highest score better than student use variated speech method. Key Words :Guide discovery-inquiry Method, Variated Speech Method, Learning Achievement.